QUALITY IN MEDICINEThe influence of sense of coherence on emotional response in heart transplant recipients – a preliminary report - Milaniak, Irena; Wilczek-Rużyczka, Ewa; Wierzbicki, Karol; Sadowski, Jerzy; Przybyłowski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: The success of heart transplantation in prolonging life and well-being must be considered in reference to its psycho-social outcomes, which intrinsically affect the long-term post-transplant morbidity. Sense of coherence and emotional response to organ reception are important factors in this group of patients. The aim of this study was to assess the contribution of sense of coherence to emotional response to transplantation in heart transplant recipients. Material and methods: The study was conducted on a group of 46 heart transplant recipients. The following research tools were applied in the assessment of personal resources (sense of coherence) and emotional response to heart transplant surgery: the Sense of Coherence Questionnaire developed by Antonovsky (SOC-29) and the Transplant Effects Questionnaire (TxEQ). The data were analyzed statistically. Results : Heart transplant recipients do not experience guilt toward the donors and have no difficulties in disclosing their identities as heart transplant recipients. The study reports good adherence to immunosuppressive treatment recommendations and both a moderate concern about and a sense of responsibility for the transplanted organs among the patients. Global SOC was associated with guilt toward the donor, concern about the transplanted heart, and disclosure of the recipient’s identity. Conclusions : The strength of the patients’ global sense of coherence is related to the level of their emotional response to the heart transplant surgery.